THE EFFECTIVENESS OF SOCIAL WELFARE PROGRAMMES IN GOVERNMENT DURING THE ECONOMIC CRISIS - Jackson Yumame; Iwan Kusnadi (CV. Adiba Aisha Amira, 2024)
The effectiveness of social welfare programmes in a time of economic crisis refers to the ability and success of government policies and initiatives in providing assistance, support and protection to people, especially vulnerable groups, to mitigate the negative impacts of economic instability. This includes the extent to which programmes can meet their objectives of maintaining living standards, reducing poverty, and sustaining people's social welfare amid significant economic challenges. The research method used in this study is literature review. The results show that social welfare programmes have a significant role in protecting people from the worst impacts of the economic crisis. Programmes such as cash transfers, food subsidies, and health insurance have proven effective in maintaining basic consumption levels and preventing an increase in poverty. However, research also identified several challenges in implementation, including budget constraints, difficulties in targeting beneficiaries, and distribution problems in remote areas. Therefore, despite these challenges, social welfare programmes remain a crucial policy instrument in dealing with the economic crisis.